PELESTARIAN BUDAYA LOKAL DALAM MATERI AJAR PENDIDIKAN JASMANI DI ERA TRANSFORMASI DIGITAL: SYSTEMATIC LITERATURE REVIEW - Hasibuan, Halim Akbar; Hasibuan , Mhd. Usni Zamzami; Diana, Fitri; Anjanika, Yonifia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Objective: This study aims to systematically examine efforts to preserve local culture through the development of digital-based Physical Education (PE) teaching materials in the era of technological transformation. Method: This study used a systematic literature review design with reference to the PRISMA 2020 guidelines. Data searches were conducted on seven scientific databases spanning 2019-2026, resulting in 24 selected studies for in-depth analysis. Results: The synthesis results show that the integration of local culture such as traditional games, folk sports, and local wisdom values ​​into digital media has proven effective in increasing learning interest and strengthening students' cultural identity. However, its implementation still faces challenges in the form of the risk of simplifying cultural meanings, limited infrastructure, and teachers' suboptimal ability to integrate cultural content, pedagogy, and technology. Conclusion: Digital transformation is a strategic opportunity for cultural preservation as long as technology acts as a supporting tool, not a substitute for the essence of culture itself. Standard guidelines and integrated training are needed so that local culture can continue to be passed down sustainably through PE learning.